2019
DOI: 10.3389/fcimb.2019.00268
|View full text |Cite
|
Sign up to set email alerts
|

HLA Upregulation During Dengue Virus Infection Suppresses the Natural Killer Cell Response

Abstract: Dengue virus (DENV) is the most prevalent mosquito-borne virus in the world and a major cause of morbidity in the tropics and subtropics. Upregulation of HLA class I molecules has long been considered a feature of DENV infection, yet this has not been evaluated in the setting of natural infection. Natural killer (NK) cells, an innate immune cell subset critical for mounting an early response to viral infection, are inhibited by self HLA class I, suggesting that upregulation of HLA class I during DENV infection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…In this study, we used an in vitro model of co‐culture to analyze the cellular and molecular events required for the control of DENV‐2 infection by NK cells. We demonstrated that infection of Mo‐DCs by DENV‐2 induced autologous NK cells to produce IFN‐γ and TNF‐α specifically, and did not mediate degranulation, in accordance with data previously observed with ex vivo NK cells of infected patients ; this is possibly explained by the upregulation of MHC class‐1 molecules, and HLA‐E in DENV‐2 infection, confirmed herein and previously described . However, we cannot exclude that the cytotoxic functions of NK cells are modulated differently in the function of the DENV serotype.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we used an in vitro model of co‐culture to analyze the cellular and molecular events required for the control of DENV‐2 infection by NK cells. We demonstrated that infection of Mo‐DCs by DENV‐2 induced autologous NK cells to produce IFN‐γ and TNF‐α specifically, and did not mediate degranulation, in accordance with data previously observed with ex vivo NK cells of infected patients ; this is possibly explained by the upregulation of MHC class‐1 molecules, and HLA‐E in DENV‐2 infection, confirmed herein and previously described . However, we cannot exclude that the cytotoxic functions of NK cells are modulated differently in the function of the DENV serotype.…”
Section: Discussionsupporting
confidence: 92%
“…4A), as described previously for different flaviviruses, and unlike many other viruses that down‐regulate MHC class‐1 expression on infected cells . Concomitantly, HLA‐E expression was significantly increased in DENV‐2‐infected cells, as described . Moreover, the frequency and surface‐expression of the MHC class‐1‐related chain (MIC)‐A and MIC‐B, two ligands of NKG2D, were significantly induced in DENV‐2‐infected Mo‐DCs ( p = 0.0015), but not in bystander Mo‐DCs, when compared to non‐infected cells (Fig.…”
Section: Resultssupporting
confidence: 73%
“…The major histocompatibility complex (MHC) is involved with both adaptive and innate immune systems, including via antigen processing and presentation, and is found in vertebrates throughout phylogeny [70]. Roles for MHC class I can also serve as an inhibitory ligand for natural killer cells and this mechanism can be exploited by viruses, which can inhibit various stages of the MHC class I antigen presentation pathway for immune evasion [71][72][73] as well as by some cancer cells, which can downregulate MHC I to avoid normal immune surveillance [74][75]. MHC I has been studied in harbour seal [76], with possible variation suggested in immune response genes in relation to susceptibility to phocine distemper virus [77] and with respect to morbillivirus infection in stranded cetaceans [78].…”
Section: Discussionmentioning
confidence: 99%
“…NK cells were purified by magnetic bead isolation via negative selection (Miltenyi, cat. 130-092-657) and stained with the NK cell antibody panel ( Supplementary Table S1) as previously described (4,23,24). Cells were resuspended in 1x EQ Beads (Fluidigm) for normalization before acquisition on a Helios mass cytometer (Fluidigm).…”
Section: Antibody Conjugation Mass Cytometry Staining and Data Acquimentioning
confidence: 99%